Hexagonal Ferrite MFe12O19 (M=Sr, Ba, Cu, Ni, Pb) Based Photocatalysts: Photoluminescence, Photocatalysis and Applications - Wang, Shifa; Yu, Xinmiao; Gao, Huajing; Chen, Xiangyu (Journal of Environmental Science and Engineering Technology, 2022)
Hexagonal ferrite (MFe12O19, M=Sr, Ba, Cu, Ni, Pb) is a kind of semiconductor material with excellent performance and an important magnetic material, with high chemical and thermal stability, low cost, simple preparation process, excellent optical, magnetic, wave-absorbing, dielectric, photoluminescence properties and catalytic activities have been widely used in broadcast communication, information storage, aerospace, automatic control, catalytic synthesis, medicine and biology and many other fields. This paper focuses on the application of MFe12O19-based ferrite in the field of photocatalysis, and further discusses the effect of preparation method on the photocatalytic activity of MFe12O19-based photocatalysts. The application of MFe12O19-based photocatalysts in the degradation of dyes, drugs and persistent organic pollutants (POPs) was deeply revealed, and the photocatalytic mechanisms of single-phase MFe12O19, ion-doped MFe12O19 and MFe12O19-based composite photocatalysts were also explored. The relationship between photocatalytic activity and photoluminescence properties of MFe12O19-based photocatalysts have also been investigated. This review points out the direction for further research on the application of MFe12O19-based photocatalysts in the field of photocatalysis.